2010
DOI: 10.3390/pharmaceutics2030275
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moisture on Powder Flow Properties of Theophylline

Abstract: Powder flow is influenced by environmental factors, such as moisture and static electricity, as well as powder related factors, such as morphology, size, size distribution, density, and surface area. Pharmaceutical solids may be exposed to water during storage in an atmosphere containing water vapor, or in a dosage form consisting of materials (e.g., excipients) that contain water and are capable of transferring in to other ingredients. The effect of moisture on powder flowability depends on the amount of wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…In contrast, the flowability of aspartame was found to increase with moisture content as the particles formed agglomerates that were that were larger and more spherical than the small and needle-shaped individual particles (16). Both Sandler et al (18) and Bravo-Osuna et al (19) found that flowability of theophylline and methyl methacrylate starch copolymers, respectively, changed with the moisture content of the powder; at low moisture levels, the water acted as a lubricant between the particles and increased the flowability while at high moisture levels, the water increased cohesion through stronger liquid bridges thereby reducing flowability.…”
Section: Introductionmentioning
confidence: 94%
“…In contrast, the flowability of aspartame was found to increase with moisture content as the particles formed agglomerates that were that were larger and more spherical than the small and needle-shaped individual particles (16). Both Sandler et al (18) and Bravo-Osuna et al (19) found that flowability of theophylline and methyl methacrylate starch copolymers, respectively, changed with the moisture content of the powder; at low moisture levels, the water acted as a lubricant between the particles and increased the flowability while at high moisture levels, the water increased cohesion through stronger liquid bridges thereby reducing flowability.…”
Section: Introductionmentioning
confidence: 94%
“…This demonstrates that for low liquid concentrations, the powder-liquid mixing process leads to a considerably better incorporation of the liquid into the solid bulk powder phase than when inserted by liquid spraying. An explanation for the lower mixibality of the sprayed water, can be the formation of liquid bridges between the particles, making them more cohesive and difficult to mix (Palzer and Sommer, 2011;Sandler et al, 2010;Kuakpetoon et al, 2001;Teunou et al, 1999).…”
Section: Evaluation Of the Powder-liquid Mixing Methodologymentioning
confidence: 99%
“…This could be attributed to the increased interparticle frictional forces, since the particles were almost stripped off of their adsorbed lubricating moisture layer at these comparatively dry conditions (30% RH) [11,41]. These increased frictional forces led to decreased relative motion of starch particles and thereby caused powder flow retardation in addition to showing the resistance to packing.…”
Section: Shear Testmentioning
confidence: 99%